Effectiveness of Financial Management of Start-Up Companies Before and After Using Virtual Account: (Case Study of PT Budi Graha Realty, The Bay Apartment Lampung) - Gabriella, Gabriella; Khairudin, Khairudin (LPPPIPublishing, 2025)
Efficient payment management is a key issue for startup companies in Indonesia, as it supports cash flow and operational sustainability. The implementation of Virtual Account payment methods is expected to improve payment efficiency and accelerate financial reporting. This study aims to examine the effectiveness of using Virtual Account at PT Budi Graha Realty The Bay Apartment by comparing receivables and reporting speed during the 2023-2024 period. A qualitative approach was used, involving interviews and document analysis. The results show that the use of Virtual Account positively affects reducing delayed receivables and accelerating financial reporting compared to traditional payment methods. These findings provide empirical evidence that the implementation of Virtual Accounts can improve financial efficiency in startup companies. It is expected that this research can serve as a reference for other companies in enhancing payments and financial management. The limitation of this study is its narrow scope, as it focuses on a single company. Future research is expected to expand the scope to test the effectiveness of Virtual Account payment methods in other companies.